Special education in science teaching - Kontopoulou, Maria-Theofania; Papageorgiou, Vasilis; Malli, Evgenia; Mertsioti, Louiza; Drigas, Athanasios (Technium Education and Humanities, 2022)
During the past years, Information and Communication Technologies (ICTs) have been studies in a large number of fields. The term ICTs refers to all kinds of technologies that let users to have access, use and manipulate information (Drigas & Ioannidou, 2013a). ICT can bridge the gap between groups of people with special (educational) needs. The growing number of researches that connects ICTs and assistive technologies (Drigas & Ioannidou, 2013), shows us that the use of them in the life of children and adults with special education needs is huge. In this part of the research we will report some of the most indicative uses of ICTs in the education of people with different learning needs (autism, visually impaired, hearing impaired/loss, sensory and physical impaired and dyslexic learners). Using ICTs and assistive technologies, involves more than overcoming environmental barriers, it is also a means of communication and expression of the personal and social characteristics of the learner. ICTs in special education (and education generally) can be used in every domain to improve it.